The Role of Husamuddin Sadr Shahid and Husamuddin Al-Ahsikati’s Scientific Heritage in Islamic Jurisprudence - Bekmirzaev, Ilhomjon; Nishanova, Dildora (The journal of contemporary issues in business and government, 2021)
The scientific heritage of two great Central Asian scholars, Husamuddin Sadr Shahid and Husamuddin al-Akhsikati, is of great importance to the Islamic Jurisprudence. An in-depth study of the scientific and spiritual heritage left by the faqihs of the Oli Moza family from Bukhara is one of the important tasks facing researchers today. This paper will detail the works and scientific heritage of Husamuddin Sadr Shahid (473/1090–536/1141), a great representative of the Ali Moza family and one of the famous Hanafi jurists, and his contemporary fellow, Husamuddin al-Akhsikati.